What's in organic wine consumer mind? A review on purchasing drivers of organic wines - Giulia Maesano; Giuseppe Di Vita; Gaetano Chinnici; Pappalardo Gioacchino; Mario D'Amico (Wine Economics and Policy, 2021)
Consumer interest in organic wine is growing, but the effects of organic label, consumer quality perception and the support for the benefits claim of organic wine are not yet fully understood and at times doubtful. The literature shows a very heterogeneous picture regarding consumer behaviour and preferences for organic wine. This study seeks to understand the link between organic wine and consumer' purchasing drivers. Using a systematic literature review, the paper explores the characteristics of consumer of organic wine, the motivation on consumer behaviour and preferences for organic wine, as well as the sensory quality and the presence of additives when evaluating wine quality and in shaping consumers' attitudes. The results show how socio-economic and psychological characteristics of consumer as well as quality perception affect their behaviour for organic wine. Little consensus on the benefits in terms of improved sensory quality of organic wine compared to conventional one. Among sensory qualities, taste has been found to be both a key driver and barrier to organic wine consumption. Based on literature studies, consumers have positive opinions toward organic wine, which is perceived as healthy and environmental friendly. However, despite the growing market interest in wine, scientific information about the organoleptic differences between conventional and organic remains scarce and the topic requires more in-depth analysis. Understanding the profile of consumer and the factors that influence consumer' behaviour provide information to the organic wine industry.
Keywords: 330; organic wine; consumer behaviour; taste; sensory quality; wine additive; sustainability; WTP